Synthesis and implementation of logic controllers – A review. (2017) - Zaytoon, J.; Riera, B.
Abstract: This paper provides an overview of some well-known formal approaches for the synthesis and implementation of logic controllers. Most of these approaches are based on the use and the adaptation/extension of the supervisory control theory of discrete-event systems. Recent contributions, based on algebraic synthesis and logic constraints are also be highlighted.